Psycholinguistic Approaches to Enhancing Arabic Speaking Proficiency through Comic Strips - Mahmudah, Menik; Nurhanifansyah, Nurhanifansyah; Khalid, Syarif Muhammad Syaheed bin (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This study explores the effectiveness of using comic strips as a psycholinguistic approach to enhance Arabic speaking proficiency (maharat al-kalam) among students. Traditional methods of teaching Arabic often emphasize grammar memorization, which can disengage students and hinder their ability to apply the language in spoken contexts. In contrast, comic strips provide a visual and narrative framework that makes learning more engaging, promoting better vocabulary retention and comprehension of sentence structures. Quantitative data was gathered through pre-tests, post-tests, and speaking tasks, while qualitative data was obtained from questionnaires and semi-structured interviews. The results showed significant improvement in the experimental group in terms of vocabulary retention, sentence structure comprehension, and speaking confidence. The visual and contextual elements of comic strips helped students internalize the language more effectively. Additionally.  However, some challenges were noted in understanding cultural contexts within the comic strips. Notably, while comics are typically used to motivate and enhance maharat al-qiro'ah (reading skills), this study found that they can also be effectively applied to improve maharat al-kalam (speaking skills) through the incorporation of Arabic vocabulary and a psycholinguistic approach.  This study concludes that comic strips offer a valuable and innovative tool for enhancing Arabic speaking proficiency, providing both cognitive and motivational benefits.